Centralisation of end of life care coordination: impact on the role of community providers - Addicott, Rachael (London J Prim Care (Abingdon), 2009)
Background The recently published End of Life Care Strategy(1) and emerging service improvements have raised the profile of end of life care (EOLC) across health and social care sectors. Policy emphasises providing patients with more choice over where they are cared for at the end of life. Surveys and anecdotal evidence suggest that the majority of people would prefer to be cared for (and die) in their own home. Such care provision evidently requires considered planning across community providers. Some areas have instigated a centralised administrative process for such care planning. Setting This shift towards centralising the administrative function of care coordination for patients who are nearing the end of life has implications for community care providers. Question This paper seeks to understand the impact that centralising EOLC care coordination in the community has had on community providers. Methods This paper draws on findings from case studies of two large primary care trust (PCT) regions in England. One hundred and two semi-structured interviews with service managers, commissioners and providers were conducted across the two case studies, as well as two focus groups (ten participants – acute and community nurses), observation of key local palliative care planning meetings, and documentary analysis of strategic and operational papers. Results The findings presented demonstrate that a centralised approach to care planning has positive outcomes for community nurses, who are able to spend more time delivering direct patient care. However, there were challenges associated with the approach – particularly the capacity of an administrative process to intelligently allocate finite resources amongst patients with a range of care needs. Conclusions The centralisation of care planning had implications for how community nurses conceptualised their role in the delivery and coordination of EOLC. Community nurses were positive regarding the alleviation of the administrative burden; however the approach challenged their professional role as key worker – particularly in making judgements as to the nature and appropriateness of patient care packages.